2009
DOI: 10.1186/1479-5868-6-54
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of eating behavior in children and adolescents: a review

Abstract: BackgroundUnderstanding the correlates of dietary intake is necessary in order to effectively promote healthy dietary behavior among children and adolescents. A literature review was conducted on the correlates of the following categories of dietary intake in children and adolescents: Fruit, Juice and Vegetable Consumption, Fat in Diet, Total Energy Intake, Sugar Snacking, Sweetened Beverage Consumption, Dietary Fiber, Other Healthy Dietary Consumption, and Other Less Healthy Dietary Consumption in children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
4
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(225 citation statements)
references
References 113 publications
13
189
4
13
Order By: Relevance
“…Student-reported measures of food security have previously demonstrated high levels of internal consistency (Cronbach α = 0·77) and statistically significant inverse associations with other measures of SES and relevant indicators of diet quality outside the school context (34) . Measures of peer modelling and parental norms were adapted from Pawlak and Malinauskas (21) and served as the psychosocial constructs examined because modelling and norms constructs are consistently associated with dietary quality in previous studies with youth (35) . Students reported their level of agreement with statements regarding what they believe their parents think they should eat (parental norms) and what they think their friends eat (peer modelling).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Student-reported measures of food security have previously demonstrated high levels of internal consistency (Cronbach α = 0·77) and statistically significant inverse associations with other measures of SES and relevant indicators of diet quality outside the school context (34) . Measures of peer modelling and parental norms were adapted from Pawlak and Malinauskas (21) and served as the psychosocial constructs examined because modelling and norms constructs are consistently associated with dietary quality in previous studies with youth (35) . Students reported their level of agreement with statements regarding what they believe their parents think they should eat (parental norms) and what they think their friends eat (peer modelling).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…1 Bahsedilen bu faktör-lerin birbirleriyle olan etkileşiminin anlaşılması sağlık-lı beslenme alışkanlığının edinilmesine yönelik daha etkili stratejilerin izlenebilmesi için oldukça önemlidir. 2 Bugüne kadar diyet kalitesinin değerlendirilmesi için farklı indeksler geliştirilmiştir. Bu indekslere, Sağlıklı Yeme İndeksi (Healthy Eating Index-HEI), Diyet Çeşit-lilik Skoru (Diet Diversity Score), Besin Öğesi Ortalama Yeterlilik Oranı (Mean Adequacy Ratio of Nutrients) ve Diyet Enerji Yoğunluğu (Dietary Energy Density) örnek verilebilir.…”
Section: Introductionunclassified
“…Conversely, research has also shown that a permissive style of parenting that allows for availability of unhealthy food products at home is linked to children eating more total fat, sugar, and 'junk food,' and consuming more soft drinks (Gable & Lutz, 2000;Haerens, et al, 2008;McClain, Chappuis, Nguyen-Rodriguez, Yaroch, & Spruijt-Metz, 2009). …”
Section: Availability Of Healthy or Unhealthy Foodsmentioning
confidence: 99%